2019
DOI: 10.3390/ijms20102500
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of CK2.3, a Novel Mimetic Peptide of Bone Morphogenetic Protein Receptor Type IA, Mediated Osteogenesis

Abstract: Background: Osteoporosis is a degenerative skeletal disease with a limited number of treatment options. CK2.3, a novel peptide, may be a potential therapeutic. It induces osteogenesis and bone formation in vitro and in vivo by acting downstream of BMPRIA through releasing CK2 from the receptor. However, the detailed signaling pathways, the time frame of signaling, and genes activated remain largely unknown. Methods: Using a newly developed fluorescent CK2.3 analog, specific inhibitors for the BMP signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 106 publications
0
25
0
Order By: Relevance
“…Additionally, our lab has developed a novel peptide, CK2.3, that also utilizes the BMP signaling pathway to induce the SMAD-dependent and SMAD-independent signaling cascades. We have previously shown CK2.3′s efficacy in multiple cell and animal models with its pro-osteoblast and anti-osteoclast effects [20][21][22]. We have also shown that CK2.3 activates ERK and SMAD signaling in C2C12 cells [22].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Additionally, our lab has developed a novel peptide, CK2.3, that also utilizes the BMP signaling pathway to induce the SMAD-dependent and SMAD-independent signaling cascades. We have previously shown CK2.3′s efficacy in multiple cell and animal models with its pro-osteoblast and anti-osteoclast effects [20][21][22]. We have also shown that CK2.3 activates ERK and SMAD signaling in C2C12 cells [22].…”
Section: Discussionmentioning
confidence: 85%
“…Activated ERK (or pERK) expression was significantly decreased after BMP2 stimulation, which indicates that SMAD independent signaling is altered in OP (Figure 1). CK2.3 has been shown to act through the ERK signaling pathway in C2C12 cells [22], and it also significantly increased expression of pERK in cells isolated from patients diagnosed with OP. This suggests that CK2.3 acts through the ERK pathway in humans as well, and that CK2.3 can rescue aberrant BMP signaling.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Park and colleagues have identified a bioactive compound, kukoamine B, from fractionation of Lycii Radicis Cortex (LRC) extract, which reverses bone loss in ovariectomized mice by enhancing osteoblast differentiation [7]. Interestingly, Vrathasha and colleagues describe how they developed a blocking peptide CK2.3 that induces osteogenesis and bone formation by acting downstream of bone morphogenetic protein receptor type IA (BMPRIA) [8]. Liao and colleagues suggest that exercise improves bone mineral density and bone microstructure in mild chronic kidney disease-mineral bone disorder (CKD-MBD) by inhibiting sclerostin production, without altering serum minerals [9], while Jeong and Kim have summarized the complex relationship between osteoporosis and chronic liver disease [10].…”
mentioning
confidence: 99%